Subfoveal Nodule Affecting Visual Prognosis in Coats Disease - Jeong, Hyun Chul; Park, Sang Jun; Joo, Kwangsic (Korean journal of ophthalmology, 2024)
Purpose: To investigate the characteristics of subfoveal nodules in Korean patients with Coats disease and their association with visual outcomes Methods: A retrospective analysis was conducted within the medical records of patients with stage 2B or 3A1 Coats disease, including clinical features, imaging, presence of either a subfoveal nodule or macular fibrosis, and visual outcome.Results: Twelve patients were present with stage 2B or 3A1 Coats disease, and nine patients (75%) presented with subfoveal nodule. Between the group without subfoveal nodule and the group with subfoveal nodule, there were no significant differences in age (mean, 14.0 ± 1.7 years vs. 27.7 ± 21.8 years; p = 0.482), sex (all men), stage of the disease (stage 2B: three patients vs. eight patients, p > 0.999; stage 3A1: none vs. one patient, p > 0.999), extension of retinal exudation (mean, 7.7 hours vs. 4.1 hours; p = 0.209) and peripheral telangiectasia (mean, 3.7 hours vs. 4.2 hours; p = 0.727), and follow-up duration (mean, 65.0 months vs. 46.1 months; p = 0.600). There were significantly more patients with severe visual loss (≤20 / 200) among the patients with subfoveal nodule (none vs. seven patients, p = 0.045), and the cause for severe visual loss was macular fibrosis in all cases. Macular fibrosis developed significantly more frequently in the patients with subfoveal nodule (none vs. seven = patients, p = 0.045).Conclusions: This study is the first study covering the analysis of subfoveal nodules in Korean patients with Coats disease. The existence of a subfoveal nodule at the initial diagnosis serves as an indicator predicting the development of macular fibrosis and a less favorable visual outcome in the patients with Coats disease. A multicenter study with a larger patient pool and further studies toward the therapeutic approach for the subfoveal nodule and macular fibrosis are needed.